Stakeholder attitudes towards and wildlife acceptance capacity for elk (Cervus elaphus) in Kansas - Noren, Karl E. (Kansas State University, 2018)
Elk in Kansas were an abundant tallgrass prairie species prior to European settlement. Elk were extirpated in the 1870s and reintroduced in the late 1980s. After three decades, wild populations continue to be low in spite of good biological conditions. Broad, low stakeholder acceptance are a suspected limiting factor. Wildlife stakeholder acceptance capacity (WSAC) and tolerance models helped to frame results from an internet based survey (n=460) directed to all Kansas counties. Respondents reported high mean positive wildlife values, acceptance for elk population increase, and significantly (p<0.05) higher personal acceptance for elk than the level of acceptance they perceived in others. Encountering wild elk in Kansas was unrelated to acceptance but strongly predicted providing wildlife habitat on private land. Hunters reported the strongest wildlife attitudes but this result was not correlated with elk acceptance. Intangible benefits (e.g. positive meaningful experiences) strongly affected (p<0.00) wildlife attitudes and elk acceptance. Tangible benefits (e.g. money) was unrelated to wildlife values but respondents who reported tangible benefits from four or more wildlife species showed higher acceptance for elk on personal property than groupings based on other variables. WSAC theory suggests social carrying capacity for elk is significantly above the current population and Kansans are more accepting of wildlife than previously thought. Wildlife managers may be encouraged by these results to conduct their own social feasibility study regarding increasing the elk population to a more ecologically sustainable level.
Keywords: Kansas; Wildlife; Attitudes; ToleranceElk